Latin American Unions and the Reform of Social Service Delivery Systems: Institutional Constraints and Policy Choice - Maria Victoria Murillo (Inter-American Development Bank, Office of the Chief Economist, 1996)
Recent policy debates on the reform of social service delivery systems focus on the decentralization of services and the introduction of competition in order to improve the quality of services. Despite the common assumption that public sector unions oppose these reforms, their responses were diverse. This paper argues that the structure of union organization and the environment of party and union competition are fundamental for understanding union policy preferences and strategic choices regarding the reforms of social service delivery systems. Mexico and Argentina education and health reforms in the early 1990s are used to illustrate the influence of these institutional features on the policy preferences and strategic choices of public sector unions.
Keywords: 330